1991
DOI: 10.1063/1.529103
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to self-similarity in Newtonian space-time

Abstract: After an introductory mathematical review of the general concept of self-similarity with respect to a given rescaling algebra, attention is focused on the case of Newtonian systems in Galilean space-time, whose self-similarity transformations will form subgroups of the maximal self-similarity group of the Galilean space-time structure itself. As a prerequisite for a systematic general investigation of self-similarity in such Newtonian systems, it is shown how an appropriately adapted similarity transporting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 7 publications
2
84
0
Order By: Relevance
“…(See Henriksen & Widrow [1999] for a discussion of the self-similar infall model based on the collisionless Boltzmann equation. This formulation [see also Carter & Henriksen 1991] allows for more general types of self-similarity. )…”
Section: Self-similar Infall Modelsmentioning
confidence: 99%
“…(See Henriksen & Widrow [1999] for a discussion of the self-similar infall model based on the collisionless Boltzmann equation. This formulation [see also Carter & Henriksen 1991] allows for more general types of self-similarity. )…”
Section: Self-similar Infall Modelsmentioning
confidence: 99%
“…They showed that it corresponds to self-similarity of the homothetic class in the context of Newtonian theory and is known as KSS of the first kind. Later, self-similarity of the second, zeroth and infinite kinds were introduced by Carter and Henriksen [11,12]. There is a great literature available [2,3,[13][14][15][16][17][18] which contain several KSS perfect fluid solutions of the EFEs.…”
Section: Introductionmentioning
confidence: 99%
“…We use, in this paper as in the previous (I, II), the Carter-Henriksen (Carter & Henriksen 1991) procedure. In this way we obtain a quasi-self-similar system of coordinates (Henriksen 2006a,b) that enables expression of the CBE-Poisson set with explicit reference to a previous transient self-similar dynamical relaxation.…”
Section: Introductionmentioning
confidence: 99%